Iron deficiency-inducible peptide-coding genes OsIMA1 and OsIMA2 positively regulate a major pathway of iron uptake and translocation in rice - Kobayashi, Takanori; Nagano, Atsushi J; Nishizawa, Naoko K (Journal of experimental botany, 2021)
Peptide-coding genes OsIMA1 and OsIMA2 are strongly induced under iron deficiency, and positively regulate a major pathway of iron uptake and translocation in rice, enhancing the iron deficiency response. Abstract Under low iron (Fe) availability, plants transcriptionally induce various genes responsible for Fe uptake and translocation to obtain adequate amounts of Fe. Although transcription factors and ubiquitin ligases involved in these Fe deficiency responses have been identified, the mechanisms coordinating these pathways have not been clarified in rice. Recently identified Fe-deficiency-inducible IRON MAN (IMA)/FE UPTAKE-INDUCING PEPTIDE (FEP) positively regulates many Fe-deficiency-inducible genes for Fe uptake in Arabidopsis. Here, we report that the expression of two IMA/FEP genes in rice, OsIMA1 and OsIMA2, is strongly induced under Fe deficiency, positively regulated by the transcription factors IDEF1, OsbHLH058, and OsbHLH059, as well as OsIMA1 and OsIMA2 themselves, and negatively regulated by HRZ ubiquitin ligases. Overexpression of OsIMA1 or OsIMA2 in rice conferred tolerance to Fe deficiency and accumulation of Fe in leaves and seeds. These OsIMA-overexpressing rice exhibited enhanced expression of all of the known Fe-deficiency-inducible genes involved in Fe uptake and translocation, except for OsYSL2, a Fe–nicotianamine transporter gene, in roots but not in leaves. Knockdown of OsIMA1 or OsIMA2 caused minor effects, including repression of some Fe uptake- and translocation-related genes in OsIMA1 knockdown roots. These results indicate that OsIMA1 and OsIMA2 play key roles in enhancing the major pathway of the Fe deficiency response in rice.